FACT vs. MEDIAFACT: a Comparative Analysis of Conceptual Models - N. A. Prom (Научный диалог)
The relevance of the study is due to the problem of the discrepancy between the constructed media reality and reality. The author sees the reason for this problem in the fact that media content producers exploit the synonymous use of the words “fact” and “media fact”. The author notes that the studies conducted earlier do not allow to clearly demonstrate the inequivalence of these concepts, therefore, indicates the need to apply the modeling method to solve this issue. It is proposed to build and then compare the conceptual models of the FACT and MEDIAFACT, taking into account the figuratively perceptual, conceptual and value sides of the concept. Attention is paid to the need to take into account the categories of absoluteness, relativity, ambivalence. The results of a comparative analysis of the learned models are presented. The importance of the media factor in the formation of the conceptual signs of MEDIAFACT is emphasized. The differentiating features of FACT (truth) and MEDIAFACT (pertinence) on the value side of the models are revealed. It is shown that the nuclear conceptual signs of the FACT (reliability and objectivity) were preserved in the conceptual model of MEDIAFACT, but moved from the absolute category to the ambivalent one. It is concluded that a comparative analysis of conceptual models made it possible to compare similar concepts of “fact” and “media fact” and demonstrate their inequivalence.